2013
DOI: 10.1016/j.jnutbio.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinases impart susceptibility to high-fat diet-induced obesity in mice

Abstract: Gelatinases play a role in adipose and muscle hypertrophy, and could be involved in tissue remodeling in response to high-fat diet (HFD) intake. This study tested potential roles of gelatinases (matrix metalloproteinses-2 and -9, MMP-2 and -9) in relationship to an antigrowth factor (myostatin, MSTN) known to be dysregulated in relation to HFD induced obesity (HFDIO) propensity. In vitro and ex vivo analyses demonstrated that MMP-9 increased mature MSTN levels, indicating a potential role of gelatinases in MST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…After 6 weeks of high‐fat feeding (60% fat), they found that up‐regulation of mRNA levels and activity of MMP‐2 and MMP‐9 were characteristic of C57BL/6 mice. In contrast, none of these changes were seen in non‐susceptible mice . Similarly, in another study using 16 weeks of HFD feeding in mice, MMP‐9 plasma activity was also increased, despite decreased protein levels in skeletal muscle .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…After 6 weeks of high‐fat feeding (60% fat), they found that up‐regulation of mRNA levels and activity of MMP‐2 and MMP‐9 were characteristic of C57BL/6 mice. In contrast, none of these changes were seen in non‐susceptible mice . Similarly, in another study using 16 weeks of HFD feeding in mice, MMP‐9 plasma activity was also increased, despite decreased protein levels in skeletal muscle .…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, in another study using 16 weeks of HFD feeding in mice, MMP‐9 plasma activity was also increased, despite decreased protein levels in skeletal muscle . MMP‐9 has been shown to be released in response to growth factors such as myostatin, thus promoting a turnover of ECM components in skeletal muscle . In contrast, Kang et al reported that despite increases in collagen III and IV protein content in gastrocnemius muscle of C57BL/6 mice after 14 to 20 weeks HFD (60% fat), MMP‐9 activity was decreased, while MMP‐2 showed no differences .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…One was FMOD, which is not only a new regulator of MSTN during myoblast differentiation but can also circumvent the inhibitory effect of MSTN and trigger myoblast differentiation [39]. Another was MMP9, which plays a role in regulating MSTN and causes muscle hypertrophy when genetically manipulated [40,41]. In the present research, through GO enrichment analysis, many genes, such as, SCX, Pax3, VTN, EOMES, PAX5, MYC, NOX4, P2RY6, ITGA2, CCL5, PGR, SRC, P2RY6, TNFRSF25, TCF7, CXCL13, SFRP1 etc., were found to be involved in the skeletal muscle cell differentiation, positive regulation of smooth muscle cell migration, regulation of cell proliferation, and negative regulation of cell growth.…”
Section: Discussionmentioning
confidence: 99%